Improving Critical Thinking Skills of Elementary School Students through Composter Innovation Learning - E. Yuliani; A S Nudzikrinia; R Setianingrum; A N Sari; Supeno Supeno (Pancaran Pendidikan, 2022)
Critical thinking is a skill that needs to be developed, practiced, and applied in the curriculum so that students are actively involved in learning. Learning activities that require students to analyze, synthesize, and evaluate information to solve problems and make decisions can sharpen critical thinking skills. The essential thinking ability of elementary school students still needs to be improved because the teacher still dominates the implementation and learning process. This study aims to improve the critical thinking skills of elementary school students through learning composter innovation. The learning was carried out during two face-to-face meetings with the learning material about composters. During the learning process, teaching and learning activities are more oriented towards student-centered learning, where students learn by observing, asking questions, and evaluating. Students also practice making composter innovations from materials obtained from the surrounding environment. Students' critical thinking is measured by using several questions posed to students. The results showed that the essential thinking ability of most of the students had increased. Learning by utilizing natural objects like this can be an alternative for teachers to improve the critical thinking skills of elementary school students